Analysis of influencing factors on sub‐synchronous oscillation of wind‐thermal‐bundled system sent out via AC/DC transmission system. Issue 16 (15th January 2019) - Wang, Yuxiao; Xu, Jianyuan; Wu, Guannan; Yu, Gaole; Zhang, Mingli; Gao, Jing; Lu, Tianqi
Abstract : Sub‐synchronous oscillation may occur when the wind‐thermal‐bundled system sent out via AC/DC transmission (WTBH) is integrated in power grid. Causing large‐scale wind‐turbine tripping, even lead the system to collapse. First, in this study the mechanism of sub‐synchronous oscillation of this system is analysed. Second, the influencing factors such as the ratio of the wind‐thermal‐bundled installed capacity, the series compensation parameters of AC transmission line, the different operating conditions of wind power etc., are analysed, which can cause different degree impact on the sub‐synchronous oscillation. Finally, the system is simulated under the Power Systems Computer Aided Design (PSCAD) environment. The results show that under the same conditions, the higher series compensation, the greater transmission capacity of the AC line, the greater risk of the sub‐synchronous oscillation. Under the condition of full load, the greater proportion of installed capacity of Doubly fed Induction Generator (DFIG) is, the less risk of sub‐synchronous oscillation; Under the lower wind speed condition, reducing the number of wind turbine can eliminate the risk of sub‐synchronous oscillation, and the oscillation frequency vary with the number of wind turbine.